Two-dimensional superconductivity and magnetotransport from topological surface states in AuSn4 semimetal - Dong Shen (Nature Portfolio, 2020)
Surface states of topological semimetals may give rise to unusual transport properties and topological superconductivity. Here, the H-T phase diagram of AuSn4 is experimentally established, displaying 2D superconductivity, Bose metal behavior, and normal-state magnetotransport driven by surface states.